Penerapan Smart Grid pada Sistem Distribusi Listrik di Sumatera Utara: Analisis Efisiensi Energi, Keandalan Pasokan, dan Tantangan Implementasi Teknologi Modern di Era Transisi Energi - Riko Putra Ananta Tarigan; Parlin Siagian; Dino Erivianto (Jurnal Nasional Teknologi Komputer, 2025)
The rapid growth of electricity demand demands an efficient and reliable electricity distribution system. Conventional distribution systems in Indonesia still face various obstacles such as high power losses, low supply fulfillment, and uneven network infrastructure. Smart grids are present as an innovative solution through the integration of information and communication technology (ICT) in distribution systems, which allows real-time monitoring and control of power flow. This study aims to examine the effect of smart grid implementation on the efficiency and efficiency of electricity distribution systems, as well as identify the challenges and benefits of implementing them in Indonesia. The research method used is a descriptive qualitative approach based on literature studies from various journals, technical reports, and related policies. The results of the study show that smart grids are able to reduce losses by 3–6% and significantly reduce SAIDI and SAIFI values. In addition, this system increases consumer participation through demand response and facilitates the integration of renewable energy. The main obstacles identified include high investment costs, limited regulations, and low public awareness of this technology. These findings are expected to be a reference in developing a more modern and sustainable electricity distribution system in Indonesia.